Comparative analysis of efficiency functioning of the controller-meliorative organization of the territory in Ukraine and the USA - Butenko, E.; Kharytonenko, R. (Land Management, Cadastre and Land Monitoring, 2017)
In order to create an optimal land use model and reduce the impact of erosion on agricultural land, a number of land conservation measures need to be introduced. The most effective set of measures that minimizes the manifestation of water erosion in erosion-hazardous areas is the contouring-reclamation organization of the territory. This complex of activities combines a protective reclamation structure that interacts with the terrain and soil protection technology of growing crops. In general, at the end of the 1980s, projects of contouring-reclamation organization of the territory were developed for sites that had a negative erosion effect throughout the territory of Ukraine. However, with the beginning of the 1990s, the practical implementation of measures to restructure the territory was suspended due to political transformations and lack of funds. In practice, one of the most striking examples of the implementation of design decisions is the territory of Lisnosankivsky village council of the Kupyansk district, whose Kharkiv territory is characterized by significant manifestations of erosion. For three decades, the staff of the soil protection laboratory conducted experiments on these sites. The possibility of achieving sustainable ecological indicators of soil erosion at field crop rotation -1.8 t / ha and soil protection crop rotation -1.5 t / ha was established. Similar objects that were implemented and implemented in the Kupyansk district of the Kharkiv region, were partially implemented on other erosion-hazardous sites in Polissya, Forest-steppe and Steppe regions of Ukraine. Today, most of these activities have exhausted their laid-out exploitation resources, some of the protected areas were destroyed as a result of the lack of state control, constant change of owners and the lack of motivation of actual land users. The negative manifestation of water erosion on arable land is characteristic not only for the territory of Ukraine. This process is widespread in different countries where the soil, relief and climatic conditions have similar characteristics of water erosion. One of the most successful foreign experience in minimizing the effects of water erosion, under similar conditions, on agricultural land is realized in the United States of America. Since the 1970s, agricultural producers (farmers) have attracted erosion-hazardous areas to cultivate and have grown crops that are in high demand on the market. Such activities have led to negative consequences. The biggest erosion problem in the early 1980s was the state of Missouri. The state of the state has a wide range of soils and terrain, which is characterized by the characteristics of water erosion and the development of a subtropical network. To stop, minimize the effects of water erosion in the United States began research and implementation of soil protection measures. In 1985, the Conservation Reserve Program (CRP) was approved. The purpose of this program was to withdraw from the cultivation of erosion-hazardous areas for 10-15 years, the development and implementation of contour-melioration organization of the territory. The funding for the CRP program was supposed by the tax on land sales. The result of this program for 30 years is the preservation of 9 billion tons of fertile soil from erosion, as well as reduced flushing of mineral fertilizers by 85%. The best results for soil conservation and minimization of the effects of water erosion across the state were achieved in Missouri. The soil washed in 2007 from 1 acre (0,405 hectares) and amounted to 4.2 tons and 5.3 tons for cultivating crops. That is, almost twice in 25 years. Approximate structure of the land fund was 1/3 of arable land, 1/3 of pasture and hayfields, and 1/3 of forest lands. This structure was achieved through the reservation of agricultural land. Domestic and foreign experience of the embodiment of contour-reclamation organization of the territory in areas with manifestation of erosion processes, testifies to the possibility of using them under arable land. However, these sites will require constant monitoring and restrictions on use. It has been practically confirmed that the key measure in the preserved soils from water erosion, in the presence of contour-land reclamation organization of the territory, will depend on the correct economic activity of the actual land user. Repeated introduction into active cultivation of erosion sites will adversely affect soil fertility and crop yield. Elimination of the consequences caused by erosion on agricultural land will not be comparable to the profits gained from cultivating crops. Keywords: сontour-land reclamation organization, erosion, water erosion, agrolandscape, land protection.